The value of vector ECG in predicting residual pulmonary hypertension in CTEPH patients after pulmonary endarterectomy - Dieuwke Luijten; Tamara Rodenburg; Harm-Jan Bogaard; Azar Kianzad; Dieuwertje Ruigrok; Philip Croon; Patrick Smeele; Hubert W. Vliegen; Anton Vonk Noordegraaf; Lilian J. Meijboom; Frederikus A. Klok (PLoS ONE, 2025)
Introduction Right heart catheterization (RHC) is the diagnostic standard for establishing residual pulmonary hypertension (PH) after pulmonary endarterectomy (PEA) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). A potential non-invasive alternative diagnostic test could be electrocardiography (ECG)-derived ventricular gradient optimized for right ventricular pressure overload (VG-RVPO). Methods We studied 66 CTEPH patients who underwent PEA. A subgroup of 20 patients also had a cardiac MRI before and after PEA. The diagnostic performance of the VG-RVPO for the detection of residual PH as well as the potential to replace RHC were assessed. Different cut-off values to define a normal VG-RVPO were evaluated. Also, we evaluated the association between mean pulmonary artery pressure (mPAP) and CMR derived indexed right ventricular (RV) mass and the VG-RVPO. Results During follow-up, 28 patients had residual PH (42%). A decrease in VG-RVPO after PEA was associated with decrease in mPAP or indexed RV mass post PEA (r = 0.55, p < 0.05 and r = 0.64, p < 0.05, respectively). If a normal VG-RVPO would exclude residual PH, the need for RHC would be reduced with 15–48%, but up to 36% of the CTEPH patients with residual PH would have been missed as they had a normal VG-RVPO. Conclusion Although there was an association between the change in VG-RPVO and changes in mPAP or indexed RV mass, our study demonstrated that VG-RPVO has limited value in excluding the presence of residual PH post-PEA as up to 36% of the CTEPH patients with residual PH would have been missed if residual PH would have been excluded based on a normal VG-RVPO.